A binomial squared is written like
![x^2+2ax+a^2](https://tex.z-dn.net/?f=%20x%5E2%2B2ax%2Ba%5E2%20)
So, we have ![2a=6 \iff a=3](https://tex.z-dn.net/?f=2a%3D6%20%5Ciff%20a%3D3%20)
So, we want to complete the square ![(x+3)^2 = x^2+6x+9](https://tex.z-dn.net/?f=%28x%2B3%29%5E2%20%3D%20x%5E2%2B6x%2B9)
We can add and subtract 9 to write
![x^2+6x = x^2+6x+(9-9) = (x^2+6x+9)-9 = (x+3)^2-9](https://tex.z-dn.net/?f=x%5E2%2B6x%20%3D%20x%5E2%2B6x%2B%289-9%29%20%3D%20%28x%5E2%2B6x%2B9%29-9%20%3D%20%28x%2B3%29%5E2-9)
Answer:
Yes
Step-by-step explanation:
7 = x
5 = y
5 = X + - 2
5 = X - 2
If X is 7 then
5 = 7-2
5=5
yes
Answer:
-7, -6, -4, -2, 0, 2, 5, 7, 8, 9
Step-by-step explanation:
Answer:
The answer is (-16.6)
Step-by-step explanation:
y/2 ≥ -8.3
y ≥ (-8.3) × 2
y ≥ -16.6
Thus, The value of y is (-16.6)
<u>-TheUnknownScientist 72</u>
Answer:
Equation: y =
x
21/2 cups of water
Step-by-step explanation:
Plug in 7 as y and 4 as x
7 = 4k
Find k
k = 7/4
Then plug k into th equation
y = 7/4 x
For the second part of the question:
Plug in x which is 6 into the bolded equation.
y = (7/4)(6) = 42/4 = 21/2 (simplified form)
21/2 cups of water